2009
DOI: 10.1111/j.1469-8986.2009.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of menstrual cycle phase on cardiac autonomic regulation

Abstract: This study investigated menstrual cycle phase differences in heart rate (HR) and RR interval variability (RRV) in 49 healthy, premenopausal, eumenorrheic women (age 30.2 ± 6.2). HR and RRV were computed from ambulatory 24-hour ECG, collected for up to 6 days, with at least one day each during early-to-mid follicular and mid-luteal menstrual phases. Phase effects on HR and RRV were assessed using linear mixed effects models with a random intercept to account for the correlation of observations within each subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 41 publications
6
57
0
Order By: Relevance
“…The BP response to sodium loading is not affected by the menstrual cycle in young women, nor is it influenced by the use of oral contraceptives [41,42]. We did study all women in the follicular phase, which has been shown to be associated with lower HR, higher SDNN and RMSSD, high frequency and low frequency than during the luteal phase, irrespective of sodium [43]. Together with our findings, it remains unclear whether dietary sodium interacts with HRV at various points in the menstrual cycle.…”
Section: Discussionmentioning
confidence: 92%
“…The BP response to sodium loading is not affected by the menstrual cycle in young women, nor is it influenced by the use of oral contraceptives [41,42]. We did study all women in the follicular phase, which has been shown to be associated with lower HR, higher SDNN and RMSSD, high frequency and low frequency than during the luteal phase, irrespective of sodium [43]. Together with our findings, it remains unclear whether dietary sodium interacts with HRV at various points in the menstrual cycle.…”
Section: Discussionmentioning
confidence: 92%
“…Previous and recent studies have demonstrated that both salt intake [6,24] and the normal menstrual cycle in women [2,23,26] can affect autonomic circulatory control. We also found recently that menstrual cycle can affect sympathetic neural responses during orthostasis in young healthy women [10].…”
Section: Autonomic Circulatory Control In Potsmentioning
confidence: 99%
“…These data will be reported elsewhere. Women were scheduled for testing during their midluteal menstrual phase to control for the effects of menstrual cycle variation on cardiac autonomic control, as described below 27. Those who completed this measurement session were randomized to either the 12‐week aerobic training program or a wait‐list control condition using random block assignment stratified by sex.…”
Section: Methodsmentioning
confidence: 99%